Managing biodiversity in agricultural ecosystems - Jarvis, Devra I. (Devra Ivy), 1959-; Padoch, Christine; Cooper, H. D. (H. David) (New York : Columbia University Press, 2007)
Describes how farmers manage, maintain, and benefit from biodiversity in agricultural production systems. Includes the most recent research and developments in the maintenance of local diversity at the genetic, species, and ecosystem levels.
Ηλεκτρονικό βιβλίο
Keywords: Agrobiodiversity; Agricultural ecology; Electronic books